(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Dengue, chikungunya, yellow fever, dengue hemorrhagic fever, malaria, encephalitis, and filariasis are some of the key issues that the Departments of Education and Health have been dealing with. Several plants repel mosquitoes in the Philippines, including oregano, which has a strong fragrant perfume. The Oregano Mosquito Repellent Lotion was created as a solution to the issues above, and it aims to determine the degree of repellency of the herbs above against mosquitoes to use them safely. This study utilized a quantitative experimental research design while employing a purposive sampling technique to accumulate 5 Dermatologists and 5 Aestheticians as respondents in assessing the level of acceptability of the project Oregano (Origanum Vulgare) as an Alternative Mosquito (Culicidae) Repellent Lotion. Using a questionnaire, the researchers conducted a survey to determine whether the project was acceptable regarding ingredients, procedural methodology, and presentation. The result of the study in terms of ingredients is acceptable. In contrast, the result of the study in terms of procedural methodology and presentation are moderately acceptable as assessed by the Dermatologists and Aestheticians. It indicates no significant difference between the assessments of the three groups of respondents in terms of the variables above. The acquired overall mean of the Dermatologists was 1.72 with a variance of 0.0872. The overall mean of the Aestheticians was 2.12 with a variance of 0.1536. The two groups of respondents acquired T- a computed value of -1.8112 and a T-critical, α=0.05, df= 8 with a value of 2.306. Therefore, the assessment of the Dermatologist and Aestheticians was Accepted. The ensuing discussions forwarded by the two groups of respondents are as follows: try to make the Oregano oil as the base instead of avocado oil, use fractionated oil to lessen the greasiness, use a pump dispenser or a squeeze bottle instead of an acrylic container, try 2/3 water phase and 1/3 oil phase, consider to use a vegetable gum or starch to increase the viscosity of the product, try to use T50 vitamin E oil or rosemary extract to add more preservatives.